A tailored intervention for the detection of patients with coronary heart disease and mental or cognitive comorbidities in the German primary care setting: qualitative evaluation of implementation success - Christin Herrmann; Belinda Werner; Florian Wurster; Ute Karbach; Charlotte Leikert; Laura Nordmeyer; Adriana Meixner; Lena Sannemann; Christian Albus; Frank Jessen; Ludwig Kuntz; Frank Schulz-Nieswandt; et al. (BMC Health Services Research)
Abstract Background Guidelines recommend the identification of potential mental and/or cognitive disorders (MCD) in patients with coronary heart disease (CHD). However, compliance with these guidelines appears to be lacking in primary care. A minimal invasive intervention was tailored with experts for the primary care setting to increase the identification of this patient group and ensure proper treatment. The intervention includes: A trigger question, screening tests and question prompt sheet for patients. Following the implementation of this intervention in primary care physician (PCP) offices, the aim of this study is to evaluate the implementation outcomes. Methods Semi-structured interviews were conducted with ten PCPs who tested the intervention for six months. The study was guided by Proctor’s Framework on Implementation Outcomes to understand the appropriateness, feasibility, acceptability, fidelity and sustainability of the intervention as proxies for implementation success. Results Relevance of the topic and the need for the intervention is recognised by all of the PCPs. All PCPs were willing to try the intervention and considered it generally appropriate and feasible. Additionally, supporting implementation resources were considered helpful in familiarising with the intervention. Screening of patients with a first diagnosis of CHD, those who have had experienced a recent coronary event and those who have been hospitalised for CHD is considered practical and appropriate. Known barriers such as lack of knowledge, perceived relevance and awareness were successfully addressed. It was not possible to overcome barriers such as time pressure, forgetfulness, and patient reaction. Additionally, the paper format of the information materials was perceived as impractical, and integration into the physician information system was identified as a possible way to increase acceptance. Nevertheless, PCPs stated they will continue to be aware of the link between CHD and MCD and want to maintain their individualised approach. Conclusions The study provides important insights into the use of a minimal invasive intervention in primary care. Despite tailoring the intervention to the primary care setting, implementation success was suboptimal due to individual barriers in PCP offices. This highlights the need for tailored approaches at the level of individual PCP offices to better address context-specific barriers.